Introduction - Panieri, Giuliana; Stiller-Reeve, Mathew; Bertolotto Bianc, Giuliano (Septentrio Educational, 2023)
An introduction to the 5 interdisciplinary lesson plans about the ocean and connecting with it via the senses that make up this booklet. The booklet was developed as part of the Advancing Knowledge about Methane in the Arctic (AKMA) Project, which is also briefly presented here.